Chemometric optimization of an HPLC method for the simultaneous analysis of a multi component drug product by the help of central composite design - Dinc-Zor, Sule; Donmez, Ozlem Aksu; Ascl, Burge; Pingo, Evridiki (ELSEVIER, 2020)
In this study, a simple, accurate, precise and rapid HPLC method was developed for the simultaneous quantification of paracetamol (PAR), pseudoephedrine hydrochloride (PSE), dextromethorphan hydrobromide (DEX) and doxylamine succinate (DOX) along with colorants; allura red (AR) and brilliant blue (BB) and sweetener; saccharine (SAC) in a syrup sample. Three indepented variables considered and their levels in Central Composite Design in order to optimize chromatographic separation conditions were as follows: Phosphate buffer ratio in mobile phase in the first gradient elution (GR1; 67, 70, 75, 80 and 83%), phosphate buffer ratio in mobile phase in the second gradient elution (GR2; 27, 30, 35, 40 and 43%) and flow rate of the mobile phase (FR; 0.9, 1.0, 1.2, 1.4 and 1.5 mL/min). Critical resolution values between SAC, PAR and PSE along with between AR and BB were used as a response. Chromatographic separation was achieved using reversed phase C18 column (4.6 mm x 250 mm x 5 mu m particle size) and the six analytes were detected with a diode array detector at 210 nm. As per the results of the optimization procedure, these optimum variables were found to be flow rate, 1.4 mL/min, phosphate buffer ratios in mobile phase in the first and second gradient elution, 75 and 40%, respectively. After optimization step, the developed method was validated in compliance with ICH guideline. Finally, the method was successfully applied to the simultaneous quantification of PAR, PSE, DEX, DOX, AR, BB and SAC in a commercial syrup sample.
Keywords: Active pharmaceutical ingredients; Colorant; Sweetener; HPLC determination; Syrup; PERFORMANCE LIQUID-CHROMATOGRAPHY; CAPILLARY-ELECTROPHORESIS; QUINOLINE YELLOW; FOOD COLORANTS; SYNTHETIC DYES; SUNSET YELLOW; PARACETAMOL; ADDITIVES; HYDROCHLORIDE; INGREDIENTS; Chemistry